Destination choice, service quality, satisfaction, and consumerism: International students in Malaysian institutions of higher education - Lim, Y.; Yap; Lee, T. (Academic Journals, 2011)
This pilot study examines the pull factors influencing international students in selecting Malaysia as the host country and their perceptions of service quality in Malaysian institutes of higher education. It has been found that students from the Middle East countries came to Malaysia mainly due to agent recommendation, lower costs, and comfortable climate. They were somewhat satisfied with their host institution. The Chinese students came to Malaysia upon the recommendation of their parents and relatives, familiarity of the country, and perceived favorable study environment. And they were somewhat dissatisfied with their host institution. These groups of students seemed to treat education as an investment and they placed importance on such factors as reputation, quality of academic staff, course content, program-related issues, costs, delivery of services, and management’s concern for them. They perceived that, overall, their host institutions were not performing satisfactory in providing quality education services. Finally, our data suggest much consumerism among these international student groups.